Absorption, tissue distribution, metabolism, and elimination of decabrominated diphenyl ether (BDE-209) in rats after multi-dose oral exposure. (November 2017) - Mi, Xiu-Bo; Bao, Lian-Jun; Wu, Chen-Chou; Wong, Charles S.; Zeng, Eddy Y.
Abstract: Human and ecological risks of BDE-209 have drawn much attention, particularly with growing e-waste recycling activities in developing countries. To further address the issue of BDE-209 biotransformation, a laboratory-controlled study was conducted. Female Sprague-Dawley rats were dosed orally by gavage at a daily dose of 1 mg kg −1 body weight for 7 d and a depuration period of 22 d, to characterize absorption, distribution, metabolism, and elimination dynamics of BDE-209 during multi-dose exposures simulating short-term oral exposure of e-waste workers. The concentrations of BDE-209 in all tissues increased exponentially during the 7-d exposure period, indicating that multi-dose exposure could lead to increased accumulation of BDE-209 in rats. The liver accumulated the greatest amount of BDE-209 on a wet-weight basis, while adipose tissue had the highest concentration by the end of the 22-d depuration period. Half-lives of BDE-209, 207, and 197 during depuration were 1.1 ± 0.1, 2.7 ± 0.3, and 10.5 ± 3.1 d in serum and 0.9 ± 0.1, 2.2 ± 0.2, and 11.8 ± 2.3 d in liver, i.e., the half-life increased with decreasing level of bromination from deca- to octa-BDEs and was similar in both serum and liver. By contrast, the half-life of the debromination metabolite BDE-207 (21.7 ± 7.7 d) was longer in small intestine than in serum and liver, suggesting slower depletion of BDE-209 metabolites in small intestine. The metabolism of BDE-209 was not responsible for the occurrence of low brominated BDE congeners and OH and MeO-PBDEs in human tissues. Graphical abstract: Highlights: The tissue distribution patterns of BDE-209 are variable between the exposure and depuration periods. BDE-209 can be transferred from small intestine to liver through blood supply, and deposit in adipose. The half-lives of BDE-209 and its metabolites are dictated by the level of bromination and tissue functionality. Abstract : Tissue-specific absorption and elimination dynamics of BDE-209 in rats are examined after multi-dose oral exposure.